Heart Rate Fails to Predict White Collar Crime - Piquero, Nicole Leeper (American journal of criminal justice, 2020)
This paper joins two strands of research: a focus on the influence of heart rate on antisocial behavior and the correlates of white-collar offending. With respect to the former, resting heart rate has been found to be one of the most replicable of all biological correlates of many different types of antisocial behavior and psychopathology. However, researchers studying the correlates of white-collar offending have only just begun to examine individual characteristics – and as of yet, have not examined the extent to which heart rate is a relevant correlate. Using data from a community sample of over a hundred males, this paper examines whether heart rate is associated with white-collar offending. Unlike other forms of antisocial behavior, the findings do not reveal a relationship between two different heart rate measures and white-collar offending. Directions for future research are noted.